Real-World Effectiveness of Dolutegravir/Lamivudine in People With HIV-1 in Test-and-Treat Settings or With High Baseline Viral Loads: TANDEM Study Subgroup Analyses - Benson, Paul; Kuretski, Jennifer; Donovan, Cynthia; Harper, Gavin; Merrill, Deanna; Metzner, Aimee A.; Mycock, Katie; Wallis, Hannah; Brogan, Andrew P.; Patarroyo, Jimena; Oglesby, Alan (Infectious diseases and therapy, 2024)
Introduction Dolutegravir/lamivudine (DTG/3TC) was first approved by the US Food and Drug Administration in 2019 for the treatment of antiretroviral therapy (ART)-naive people with HIV-1 based on results from the pivotal GEMINI-1/GEMINI-2 trials. Around that time, immediate initiation of treatment upon diagnosis was recommended in the US Department of Health and Human Services guidelines. Here we report results from 126 treatment-naive people with HIV-1 who initiated DTG/3TC as part of a test-and-treat strategy ( n = 61) or with high baseline viral loads (HIV-1 RNA ≥ 100,000 copies/ml; n = 16) from the TANDEM study. Methods TANDEM was a US-based, retrospective chart review study that included a cohort of 126 individuals aged ≥ 18 years with no prior history of ART who initiated DTG/3TC before September 30, 2020, and had ≥ 6 months of follow-up. Test-and-treat was defined as ART initiation shortly after diagnosis without available viral load, CD4 + cell count, or HIV-1 resistance data. Outcomes included virologic suppression (HIV-1 RNA < 50 copies/ml; overall and by baseline viral load) and discontinuations. Analyses were descriptive. Results Among 61 individuals who initiated DTG/3TC in a test-and-treat setting (median [interquartile range (IQR)] treatment duration, 1.3 [0.9–1.7] years), 57 (93%) achieved virologic suppression, and 51 (84%) remained suppressed; 1 (< 1%) individual discontinued DTG/3TC due to persistent low-level viremia. The most common healthcare provider (HCP)-reported reason for initiating DTG/3TC was avoidance of long-term toxicities among individuals in the test-and-treat subgroup. Of 16 treatment-naive individuals with high baseline viral loads (median [IQR] treatment duration, 100,000–250,000 copies/ml: 1.2 [0.8–1.8] years; > 250,000 copies/ml: 1.0 [0.7–1.1] years), 14 (88%) achieved virologic suppression, 13 (81%) remained suppressed, and none discontinued DTG/3TC. Patient preference was the most common HCP-reported reason for initiating DTG/3TC in this subgroup. Conclusions Results demonstrate real-world effectiveness of DTG/3TC, with few discontinuations, in people with HIV-1 in test-and-treat settings or with high baseline viral loads.